2020
DOI: 10.3390/toxics8030047
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure and Associations with Hyperlipidemia and Elevated Liver Enzymes: A Nationwide Cross-Sectional Survey

Abstract: Mercury (Hg) has obesogenic properties. However, the associated health outcomes of population-level mercury exposure were unclear. This study investigated the relationships between blood mercury levels and obesity-related outcomes such as hyperlipidemia and elevated liver enzymes. Using the second cycle of the Korean National Environmental Health Survey (n = 6454), we performed logistic regression to examine the effects of Hg on hyperlipidemia and elevated liver enzymes. The blood mercury levels were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…Another study found that TC and LDL-C levels were 1.5–2.0 and 1.6–2.4 times higher ( p < 0.001) in the occupational Pb exposure group (27.00–48.90 μg/dL for BPb) than in the control group (15.78 μg/dL for BPb), whereas TG and HDL-C levels did not show a significant association ( p < 0.05) [ 49 ]. Furthermore, a study using the KoNEHS observed that BHg concentrations are significantly higher in the hyperlipidemia group (4.03 and 2.83 μg/L for male and female) than that in the non-hyperlipidemia group (3.48 and 2.69 μg/L of male and female), and individuals with higher BHg concentrations have a 11% higher risk of hyperlipidemia [ 50 ]. Significant increases in TC, HDL-C, and LDL-C levels are reported with increasing BHg concentrations in Korean adults, based on the KoNEHS [ 40 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that TC and LDL-C levels were 1.5–2.0 and 1.6–2.4 times higher ( p < 0.001) in the occupational Pb exposure group (27.00–48.90 μg/dL for BPb) than in the control group (15.78 μg/dL for BPb), whereas TG and HDL-C levels did not show a significant association ( p < 0.05) [ 49 ]. Furthermore, a study using the KoNEHS observed that BHg concentrations are significantly higher in the hyperlipidemia group (4.03 and 2.83 μg/L for male and female) than that in the non-hyperlipidemia group (3.48 and 2.69 μg/L of male and female), and individuals with higher BHg concentrations have a 11% higher risk of hyperlipidemia [ 50 ]. Significant increases in TC, HDL-C, and LDL-C levels are reported with increasing BHg concentrations in Korean adults, based on the KoNEHS [ 40 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on assessing the impact of Hg exposure on health, but the outcome continues to be unclear. Investigations around effect of Hg exposure on obesity-related outcomes, elevated liver enzymes, cardiometabolic risk are documented (Lee et al, 2020; Poursafa et al, 2014). Epidemiological studies focused on assessing the impact of Hg exposure on liver function have shown inconsistent results, including one from the Minamata area, polluted with methylmercury.…”
Section: Discussionmentioning
confidence: 99%
“…In this Special Issue, entitled “Toxic Metals, Chronic Diseases and Related Cancers”, there are 19 published manuscripts, including reports of environmental exposure monitoring [ 1 , 2 ] and food safety surveillance [ 3 , 4 ]; reviews focusing on health risks of chronic exposure to cadmium and lead [ 5 ], experimental studies on the toxicity of cadmium, lead or mercury in gonads [ 6 ], and evidence that cadmium exposure may be one of the environmental factors contributing to hyperglycemia, insulin resistance and diabetes [ 7 ]; a mathematical model of the oral glucose tolerance test [ 8 ]; epidemiological studies examining health impacts of cadmium, lead, and mercury [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]; and reports concerning the immunotoxicity of high exposure to lead [ 16 ], the effects of cadmium on protein reabsorption by kidney tubular epithelial cells [ 17 ], the cytotoxicity of hexavalent chromium [ 18 ], and the carcinogenicity of aluminum in vivo [ 19 ].…”
mentioning
confidence: 99%
“…In a study of 311 children (151 girls and 160 boys), aged 3–7 years, from a coastal area of Thailand, Yimthiang et al report a 2-fold increase in the risk of stunted growth among children who had high blood lead levels (≥5 µg/dL) [ 14 ]. Milk consumption reduced the risk of abnormal growth by 43%.…”
mentioning
confidence: 99%
See 1 more Smart Citation